Light in The Qur’an: Ibn Sina’s Psycho-Philosophical Interpretation on The Surah Al-Nūr [24:35] - Humaidi Humaidi; Yusuf Rahman (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2023)
This article explains and analyzes the position and function of the soul for humans and its relationship to the Supreme Being in Ibn Sina’s interpretation of the Qur’an, Q.S. al-Nur [24:35]. According to Ibn Sina, the soul is the same as light, nur, and non-physical being that becomes a source of knowledge, enlightenment, and truth. The method used by Ibn Sina in interpreting this verse, Q.S. al-Nur [24:35], can be classified into rational or manhaj al-ijtihad al-’aqli. Meanwhile, the scope of the study focuses on the existence, potential, and actualization of the human soul, which originates in the Universal Being, Allah SWT. The analysis concludes that Ibn Sina’s rational-psychological interpretation is the first in the history of tafsir. This conclusion also responds to the accusation that Ibn Sina’s interpretation is misleading, distancing Muslims from the Islamic creed. This qualitative library research applied a rational and historical approach and analysis.